(untitled) (Research, Society and Development, 2021)
Practical classes are essential for understanding the contents of the Biology area, especially Botany. This article aimed to present a teaching methodology in the field of botany, based on a practice carried out by PIBID students at the Federal University of Piauí - CSHNB, as well as to bring reflections on the knowledge related to methodologies in this area. To carry out this work, a field research methodology was adopted and then a qualitative and quantitative analysis, using a form of perceptions from the students’ verbal and non-verbal communication and their involvement in the class, such as behaviors , questions, body expressions and comments. The results obtained were the participation of all students in the class, who were able to visualize and distinguish the various groups of plants studied within the teaching of Botany through live specimens and some plant structures collected in the region close to the school, which brought the content closer to the students’ reality. In addition, several scientific works address the need to work the practical part of the contents within the social context of the students, which corroborates the realization of this study aiming to demonstrate the importance of the practice for the significant teaching and learning.